(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present Paper, entitled “A Study on the Structures of Nuclei and Nuclear Thermodynamics”, Focuses On The Structure of Nuclei in The Nuclear Physics and nuclear thermodynamics in the particles and nuclei. The first part of the paper shows Nuclei that are in their ground state or are only slightly excited are examples of degenerate Fermi gases. The nuclear density is determined by the nucleon interaction – essentially by the strong repulsion at short distances and the weak attraction between nucleons that are further apart. The average distance between the nucleons is much larger than the radius of the nucleon hard core. Up to now we have concerned ourselves with the properties of nuclei in the ground state or the lower lying excited states. We have seen that the observed phenomena are characterised, on the one hand, by the properties of a degenerate fermion system and, on the other, by the limited number of the constituents. The nuclear force generates, to a good approximation, an overall mean field in which the nucleons move like free particles.